ENERGY EXPENDITURE OF TYPE-SPECIFIC SEDENTARY BEHAVIORS ESTIMATED USING SENSEWEAR MINI ARMBAND: A METABOLIC CHAMBER VALIDATION STUDY AMONG ADOLESCENTS (Kinesiology, 2018)
SenseWear Mini Armband, an accelerometer with multiple physiological sensors, could be a practical means to estimate energy expenditure (EE) of children and adolescents, but its validity reported for these age groups has not been consistent within the literature. EE of twenty-six healthy Chinese 12-year-old adolescents was measured simultaneously using both SenseWear Mini Armband (SWMA) and metabolic chamber (MC) during a 16-hour stay in a MC. SWMA systematically underestimated the adolescents’ EE during sedentary behaviors, resting metabolic rate (RMR), basal metabolic rate (BMR), and total EE, with the absolute error rate ranging from 14.85% to 28.65%. The SWMA significantly underestimated EE compared with MC in Chinese adolescents. However, the amount of error can be reduced by applying correction equation proposed in this study.Key words: sitting, physical inactivity, accelerometer, activity monitor, whole-room calorimetry